The role of gerontologist at a university of the third age: a case study - Silva, Paula Fernanda Carlos da (2015)
This paper presents the Gerontologist’s practice at a University of the Third Age in the countryside of SP/BR. The aim is to describe the gerontologist professional portfolio in this context and discuss the different models of Universities of the Third Age in different parts of the world. A systematic review of the current available literature was conducted and synthesized. In addition, the management plan conducted by undergraduate students on Gerontology is described and commented in order to discuss the practice at Universities of the Third Age.